Reminder PE#01 Price escalation for plumbing pipes and electricity cable works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder on price escalation for plumbing pipes and electricity cable works of BRACU new campus project.